Dengue induces iNOS expression and nitric oxide synthesis in platelets through IL-1R - Pinheiro, Mariana Brandi Mendonça; Rozini, Stephane Vicente; Quirino-Teixeira, Anna Cecíllia; Barbosa-Lima, Giselle; Lopes, Juliana F.; Sacramento, Carolina Q.; Bozza, Fernando A.; Bozza, Patrícia T.; Hottz, Eugenio D. (Frontiers in Immunology, 2022)
Dengue is an arthropod-born disease caused by dengue virus (DENV), that may manifest as a mild illness or severe form, characterized by hemorrhagic fever and shock. Nitric oxide (NO) is a vasodilator signaling molecule and an inhibitor of platelet aggregation known to be increased in platelets from dengue patients. However, the mechanisms underlying NO synthesis by platelets during dengue are not yet elucidated. IL-1β is a pro-inflammatory cytokine able to induce iNOS expression in leukocytes and present in dengue patients at high levels. Nevertheless, the role of IL-1β in platelet activation, especially regarding iNOS expression, are not clear. In this study, we confirmed that platelets from dengue patients express iNOS and produce higher levels of NO during the acute phase compared to healthy volunteers, returning to normal levels after recovery. Platelet NO production during acute dengue infection was associated with the presence of warning signs, hypoalbuminemia and hemorrhagic manifestations, suggesting a role in dengue pathophysiology. By investigating the mechanisms, we evidenced increased iNOS expression in platelets stimulated with dengue patients´ plasma, indicating induction by circulating inflammatory mediators. We then investigated possible factors able to induce platelet iNOS expression and observed higher levels of IL-1β in plasma from patients with dengue, which were correlated with NO production by platelets. Since platelets can synthesize and respond to IL-1β, we investigated whether IL-1β induces iNOS expression and NO synthesis in platelets. We observed that recombinant human IL-1β enhanced iNOS expression and dose-dependently increased NO synthesis by platelets. Finally, platelet infection with DENV in vitro induced iNOS expression and NO production, besides the secretion of both IL-1α and IL-1β. Importantly, treatment with IL-1 receptor antagonist or a combination of anti-IL-1α and anti-IL-1β antibodies prevented DENV-induced iNOS expression and NO synthesis. Our data show that DENV induces iNOS expression and NO production in platelets through mechanisms depending on IL-1 receptor signaling.